EEG analysis of opioid-dependents after methadone maintenance / Maysam Oladazimi - Maysam, Oladazimi (2011)
Brain function could be changed by usage of opioids. This report presents electroencephalographic (EEG) power analysis across the several frequency bands (Alpha (8-12), beta (13-24) and Gamma (25-45)) for opioids. Power analysis is a feature has been used in this study for brain function examination. First of all the raw EEG data took by 19 channel EEG machine with the help of neuro-scan soft ware. After that the preprocessing has been done on raw data for removing artifact by Independent Component Analysis (ICA). Also data analysis has been done with Spss Software to compare the results. The body composition has measured for this project by Bio Dynamics Model 450. The project been conducted on four heroin addicts’ patients whom start to withdrawal by methadone. This was a pilot study because previous research just applied to the subjects who were under methadone maintenance (MM). This study works on the addicts’ patients who just start to withdrawal by methadone and measured brain power alteration. The results show that changes in brain power in Alpha frequency band after taking methadone had been increased and also the same situation for Gamma frequency band had been occurred. But in case of Beta frequency band power had decreased. By comparison with the healthy subjects, this changes from the physiologically aspect means that our addicts subjects by administration of methadone going back to the normal situation. For Body Composition Analysis (BIA) result presents that after taking methadone there was significant increase in Phase Angle (PA), Resistance (Res.), Body Capacitance (BC) and Body Cell Mass (BCM).